Logic : a complete introduction - Lee, Siu-Fan (Great Britain Hooder & Stroughton, 2017)
Introduces three basic logical systems: categorical logic, propositional logic, and predicate logic, identifying in each system essential methods to test arguments and offering illustrations and exercises to assist the reader in mastering these skills.
Keywords: Logic -- Popular works; PHILOSOPHY -- Logic; Logic